KELUAR DARI LINGKARAN CSR: CORPORATE SOCIAL ENTREPRENEURSHIP DALAM MENJAWAB TANTANGAN SOSIAL LICENSE TO OPERATE [GETTING OUT FROM THE CIRCLE OF CSR: CORPORATE SOCIAL ENTREPRENEURSHIP IN ANSWERING THE CHALLENGE OF SOCIAL LICENSE TO OPERATE] - Vandy Yoga Swara; Erwinton Simatupang (Universitas Pelita Harapan, 2020)
Many believe that corporate social responsibility (CSR) is able to present social license to operate (SLO) of company’s community and stakeholders. In fact, CSR is not in line with SLO. The root of the problem lies on a CSR approach that differenciates economic and social value. Therefore, pressure, expectation, and need of company’s community and stakeholder will not be able to be met by a corporation despite it has proposed the best CSR programs. Through a series of literature reviews on SLOs and case studies at one company, this article offers an alternative approach to present SLO on business by emphasizing corporate social entrepreneurship (CSE) spirit.